Penguatan Digital Culture Siswa dalam Meningkatkan Literasi Digital: Pendekatan Teoritis dan Praktis - Selly Anastassia Amellia Kharis; Melisa Arisanty; Gunawan Wiradharma; Anton Robiansyah; Edward Zubir; Sri Sukatmi; Sri Maulidia Permatasari (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Good digital literacy skills are essential in the digital era. One crucial element of digital literacy is digital culture. Digital culture needs to be instilled from en early age to prevent the negative impacts of digital transformation. This activity aimed to enhance digital literacy, particularly digital culture, among students at SMP PGRI 1 Ciputat. The activity involved 40 student representatives who are members of the Organisasi Siswa Intra Sekolah (OSIS). The program was in the form of a training session that covered both theoretical and practical applications, including material on digital literacy, social media communication ethics, and data security. The results showed an improvement in students’ understanding of the concept of digital culture. Through this activity, students are expected to become more conscious and responsible technology users and participate positively in the digital society.